Virtual Sensorimotor Training for Balance: Pilot Study Results for Children With Fetal Alcohol Spectrum Disorders. Issue 4 (2016) - Jirikowic, Tracy; Westcott McCoy, Sarah; Price, Robert; Ciol, Marcia A.; Hsu, Lin-Ya; Kartin, Deborah
Abstract : Purpose: To examine the effects of Sensorimotor Training to Affect Balance, Engagement, and Learning (STABEL), a virtual reality system to train sensory adaptation for balance control, for children with fetal alcohol spectrum disorders (FASDs). Methods: Twenty-three children with FASDs received STABEL training in a university laboratory, or home, or were controls. The Movement Assessment Battery for Children–2nd edition (MABC-2) and Pediatric Clinical Test of Sensory Interaction for Balance–2 (P-CTSIB-2) were analyzed by group (lab, home, and control), session (pre-STABEL, 1 week post-STABEL, and 1 month post-STABEL), and group-by-session interaction. Results: Significant effects were group and session for MABC-2 Balance and interaction for MABC-2 Total Motor and P-CTSIB-2. Conclusion: Preliminary results support improved sensory adaptation, balance, and motor performance post-STABEL, which warrant further study with a larger, randomized sample. Abstract : An examination of the effects of Sensorimotor Training to Affect Balance, Engagement, and Learning, a virtual reality system to train sensory adaptation for balance control, for children with fetal alcohol spectrum disorders.